(3GdeSfO GdUMjM GdMSf aj eBKQ CHj GdMSf (B( (3Ydi Hf CHj SYjO GdeQjfi (B)s - (3eMeO Hf CMeO Hf eMeO Hf eQRhb GdYLjSj CHh YHO Gddg , GHf eQRhb , TeS GdOjf,J (B781 (3g` s
(3ChdgG (B:s
(3jHOC HGdaUd GdChd ef ebOeI GdcJGH ai MbjbI GdNdGaI dZI hTQYkG s
(3BNQgG (B:s
(3jfJgi HGdaUd GdKGef ef NGJeI GdcJGH ai JegjO CYPGQ Yf CehQ hbYJ ai gPG GdJCdja s
(3HgG fXGe GdJYbjHIs
(3fSNI Je fbdgG Yf fSNI ESchQjGds
(3HBNQg agQSJ dcJGH GdeSfO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B16s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs